PERBANDINGAN TINGKAT PROFITABILITAS DAN LIKUIDITAS DARI ASSET-LIABILITIES MANAGEMENT PADA BANK SYARIAH DAN BANK KONVENSIONAL - Rindang Nuri Isnaini Nugrohowati (JESI (Jurnal Ekonomi Syariah Indonesia), 2015)
Abstract The banking sector has a very important position for the economic systemof a country. The banking system, which is part of the financial system willaffect the course of the economic system as a whole. If the banking system isweak then the system will also be weak economy. Banking is an intermediaryinstitution is the institution that channel funds from surplus funds (surplusunits) to the sectors that lack of funds (deﬁ cit units). With the banking economic actors in need of funds can be met so that the economy can continue to run. In this study will speciﬁ cally analyze the comparison of the level of proﬁ tability of the asset-liability management in Islamic banks and conventional banks are seen from the return on assets and return on equity rises. It also will be studied comparative level of liquidity in Islamic banks and conventional banks are seen from the loan to deposit ratio and Capital Adequacy Ratio. By Hyphothesis is as follows : Ha1: there are differences in the level of profitability of the asset-liabilitymanagement in Islamic banks and conventional banks are seen from the return on assets and return on equity Ha2: there are differences in the level of liquidity in Islamic banks andconventional banks are seen from the loan to deposit ratio and Capital Adequacy Ratio Data analysis has been done obtained the following conclusions, based onmeans testing compare with test Independent-Samples t-test showed that the level of tability seen from ROA and ROE between Islamic Bank and Bank Konvensiona show any signiﬁ cant difference. This is demonstrated by tests of signiﬁ cance 0.02 0.05 for FDR, while for the signiﬁ cance test CAR of 0.38> 0.05. Keyword: Proﬁ tabilitas, Likuiditas, Asset Liabilities Management, Bank Syariah